The Study of {99}mTc-Aluminum Oxide Using for Sentinel Lymph Nodes Detection in Experiment; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Medvedeva А. А. Anna Aleksandrovna; Sinilkin I. G. Ivan Gennadjevich; Zelchan (Zeltchan) R. V. Roman Vladimirovich; Chernov V. I. Vladimir Ivanovich; Lyapunov A. Yu.; Bragina O. D. Olga Dmitrievna; Varlamova N. V. Natalya Valeryevna; Skuridin V. S. Viktor Sergeyevich; Dergilev A. P. (2016, 2016)
Title screen